Optimization of methylene blue photodegradation by Cr-PTCHIna/TiO2 composite using box-behnken design application - Adawiah Adawiah; Soniah Fitriani; Leni Andriyani; Yulyani Nur Azizah; Wahyudin Wahyudin; Dede Sukandar; Agustino Zulys (Sustainable Chemistry for Climate Action)
The Cr-PTCHIna/TiO2 composite synthesized using an isonicotinic acid modulated chromium and perylene-based metal-organic framework (Cr-PTCHIna MOF) and titanium oxide (TiO2) showed promising results for the photodegradation of methylene blue. The composite was synthesized through the solvothermal method with a molar ratio of Cr and Ti of 1:1 mmol. The XRD diffraction patterns of Cr-PTCHIna/TiO2 composite showed sharp peaks at 2θ = 12°, 25°, 27°, 37°, 48°, 54°, 55°, and 62° with crystal sizes of 14.144 nm. The Cr-PTCHIna/TiO2 composite has a band gap energy of 2.02 eV and a rod-shaped morphology with a particle size of 239.16 nm. The Box-Behnken Design (BBD) demonstrated that the composite can achieve an optimum degradation efficiency of methylene blue of 88.55 % under methylene blue initial concentration of 35.7 ppm, pH 6.6, and photocatalyst mass of 0.13 % under 250-watt Mercury lamp irradiation for 2 h.